Tennis Medicine A Complete Guide to Evaluation, Treatment, and Rehabilitation (Springer International Publishing, 2018)
This book will serve as a key resource for all clinicians working in orthopedics, sports medicine, and rehabilitation for the sport of tennis. It provides clinically useful information on evaluation and treatment of the tennis player, covering the entire body and both general medical and orthopedic musculoskeletal topics. Individual sections focus on tennis-related injuries to the shoulder, the elbow, wrist, and hand, the lower extremities, and the core/spine, explaining treatment and rehabilitation approaches in detail. Furthermore, sufficient sport science information is presented to provide the clinical reader with extensive knowledge of tennis biomechanics and the physiological aspects of training and rehabilitation. Medical issues in tennis players, such as nutrition and hydration, are also discussed, and a closing section focuses on other key topics, including movement dysfunction, periodization, core training, and strength and conditioning specifics. The expansive list of worldwide contributors and experts coupled with the comprehensive and far-reaching chapter provision make this the highest-level tennis medicine book ever published.